Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Appendix A - Exercise Set: 6

Answer

$ - 13 z^4$

Work Step by Step

$-\frac{26z^{11}}{2z^{7}} = -\frac{13z^{11}}{z^{7}} = -\frac{13z^{11-7}}{1} = -\frac{13z^4}{1} = - 13 z^4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.